Assessing the Fulfillment of Transwomen Sex Workers’ Social, Cultural, and Economic Rights in Yogyakarta: A Capabilities Approach-Based Study - Manik, Putu Ratna Indriyani; Tama, Berlian Widya; Karima, Hafizhah Laila; Raya, Rio Anugrah; Herlambang, Yoanita Putri; Utami, Rona (Jurnal Filsafat "WISDOM", 2024)
Transwomen community in the Special Region of Yogyakarta (Yogyakarta) faces distress in obtaining their social, cultural, and economic rights as part of the society. The stigma attached to them as non-conforming in the midst of Indonesian people with a majority of binary genders causes discrimination. It becomes difficult for them to access healthcare services, deal with civil registration matters, and getting proper job opportunities that often leads many of them to end up as sex workers. Although those rights should be guaranteed by the state. This research aims to analyze the implementation of equality principles based on Nussbaum’s capabilities approach theory by examining the fulfillment of the transwomen sex workers’ social, cultural, and economic rights in Yogyakarta. In-depth interview method is used for collecting empirical data. While data analysis is done through a case study approach. It is concluded that the social, cultural, and economic rights of transwomen sex workers in Yogyakarta have not been fulfilled thoroughly since only the capabilities of life, bodily health, senses, imagination, and thought, emotions, practical reason, affiliation, and other species are fulfilled. However, control over one’s environment in political context, bodily integrity, and play capabilities were not.